2000
DOI: 10.1046/j.1526-4610.2000.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Factors Associated With Migraine in Schoolchildren

Abstract: .-Headache and migraine are common in childhood and may be influenced by social, familial, environmental, and psychological factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
3
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 22 publications
(52 reference statements)
11
88
3
9
Order By: Relevance
“…These symptoms are common in school health and are considered major psychosomatic symptoms in association with stress (45,46), and also noise (47). These symptoms are also considered more prevalent among girls (48).…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms are common in school health and are considered major psychosomatic symptoms in association with stress (45,46), and also noise (47). These symptoms are also considered more prevalent among girls (48).…”
Section: Discussionmentioning
confidence: 99%
“…35,49 Children are spending increasing amounts of time with information technology equipment and electronic entertainment, which can cause static strain in the neck/shoulder area easily. Bener et al 50 found that, among school children, the most common environmental factor provoking migraine attacks was playing with a computer.…”
Section: E438mentioning
confidence: 99%
“…31 An epidemiological study of bronchial asthma among children in Moscow found that children living near perfume factories had a higher incidence of asthma. 32 A review of the literature by the Institute of Medicine categorized exposures as to their impact on triggering and causing asthma.…”
Section: Respiratorymentioning
confidence: 99%